High heat resistant fluorinated silicone rubber material and method for producing the same
Patent Information
- Application Number
- CN202611098710.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的首先是为了解决现有氟硅橡胶在200℃以上长期热氧老化条件下,由于主链解聚及侧链氧化导致压缩永久变形大幅升高、材料变硬发脆及弹性密封功能迅速丧失的技术问题
本发明提供的一种高耐热氧化氟硅橡胶材料及其制备方法,通过水杨醛亚胺基乙烯基氟硅油与复配超分子络合高效热氧稳定剂的配比和工艺协同,在橡胶基体内部成功构筑了共价交联与动态可逆配位交联的双网络互锁结构。结合表1的宏观检测数据,本发明相对于现有技术具有以下技术效果及机理表现:
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of rubber materials technology, specifically relating to a high heat-resistant oxidized fluorosilicone rubber material and its preparation method. Background Technology
[0002] Fluorosilicone rubber (FVMQ) is a special elastomer in which fluorinated groups (such as trifluoropropyl groups) are introduced onto the side chains of polysiloxane molecules. It combines the excellent properties of silicone rubber, such as high and low temperature resistance and hydrophobicity, with those of fluororubber, such as solvent and oil resistance. Currently, FVMQ is widely used in high-precision fields such as aerospace, defense, rail transportation, and the automotive industry, playing an irreplaceable role, especially in the manufacture of high-performance dynamic seals, static seals, fuel pipelines, and various media-resistant gaskets. Its service stability and lifespan in high-temperature air / oil media directly affect the overall operational safety of equipment systems.
[0003] However, in extremely harsh service environments such as aerospace and modern automotive engine compartments, operating temperatures continuously rise (often facing high-temperature zones exceeding 180°C or even 200°C), and the materials are exposed to hot and oxidative atmospheres for extended periods. Existing fluorosilicone rubber materials (such as traditional formulations using only common iron oxide red as a heat stabilizer) are highly susceptible to depolymerization and degradation of the main molecular chain (i.e., a "biting-back" degradation reaction generating cyclic siloxanes) under long-term hot and oxidative aging, and side chain groups may also undergo oxidative cross-linking or breakage. This leads to a rapid increase in the rubber material's compression set and a significant decrease in its retention rate during long-term service. The material gradually hardens, becomes brittle, or develops a sticky surface, thus losing its elastic sealing function, causing media leakage, and posing a safety hazard to the operation of high-end equipment.
[0004] In response to this situation, there is an urgent need to develop a fluorosilicone rubber material with higher resistance to heat and oxygen aging. Extending the effective service life of fluorosilicone rubber in extreme heat and oxygen environments and reducing its permanent compression deformation under long-term pressure are pressing issues for solving the technical bottlenecks currently faced by high-end manufacturing equipment in the field of high-temperature sealing. This is of paramount importance and practical significance for improving the safety and reliability of pillar industries such as aerospace in my country. Summary of the Invention
[0005] The primary objective of this invention is to address the technical problems of existing fluorosilicone rubbers under long-term thermo-oxidative aging conditions above 200°C, which result in a significant increase in permanent compression set, material hardening and brittleness, and rapid loss of elastic sealing function due to main chain depolymerization and side chain oxidation.
[0006] Meanwhile, this invention introduces coordination chemistry and supramolecular "sacrificial bond" energy dissipation theory to address key technical deficiencies inherent in existing high-heat-resistant fluorosilicone rubber solutions for addressing the aforementioned thermo-oxidative aging: (1) "Stabilizer extraction and loss" phenomenon under high temperature medium environment: Conventional thermo-oxidative stabilizers and small molecule structure control agents are only physically adsorbed or weakly hydrogen bonded to the rubber matrix. Under long-term immersion in high temperature aviation fuel, lubricating oil and other media, they are easily extracted and lost, causing the rubber material to shrink and harden drastically in the middle of service, and the thermo-oxidative resistance to drop sharply. (2) The mutual antagonism between processing safety and dynamic flexural fatigue life: Although the introduction of conventional active strong alkaline inorganic metal oxides can capture acid, they are very easy to catalyze the early decomposition of peroxides, resulting in a very short scorch time. Furthermore, the rigid powder aggregates are very easy to cause stress concentration, leading to early cracking of the material during repeated dynamic flexural processes.
[0007] This invention achieves a breakthrough in the aforementioned multiple technical bottlenecks by deeply reconstructing the supramolecular structure of two core raw materials and constructing a dual-network interlocking structure of covalent crosslinking and dynamic reversible coordination crosslinking inside fluorosilicone rubber.
[0008] To achieve the above objectives, the present invention provides a high heat-resistant oxidized fluorosilicone rubber material, comprising the following raw materials in parts by weight: Fluorosilicone raw rubber (brand name FSE7560, Momentive Corporation, USA): 100 parts; Hydrophobic fumed silica (Aerosil R972, Evonik Industries AG, Germany): 25-35 parts; Salicylaldehyde imine vinyl fluorosilicone oil: 3-6 parts; Compound supramolecular complex high-efficiency thermo-oxidative stabilizer: 4-9 parts; 50% by mass of bis(2,5) sulfide paste (product of Noryon Chemicals Co., Ltd.): 0.8 to 1.5 parts.
[0009] To construct a dual network of chemical covalent and highly stable supramolecular coordination, the key raw material specifications and modification methods for the two improvements mentioned above are limited as follows: 1. Salicylaldehyde imine vinyl fluorosilicone oil: Industrial grade, molecular weight 3000-4500, kinematic viscosity 400-600 mPa·s, terminal hydroxyl mass fraction 3.8%-5.2%, side chain contains unsaturated vinyl groups (mass fraction 1.2%-2.2%) and salicylaldehyde imine functional groups (mass fraction 1.8%-3.2%).
[0010] The preparation method of this raw material is as follows: commercially available industrial-grade side-chain aminopropyl vinyl fluorosilicone oil and anhydrous salicylaldehyde (commercially available, purity ≥99.5%) are reacted in anhydrous ethanol medium at 40-50°C for 3-4 hours with an equimolar ratio of amino to aldehyde groups. Then, the ethanol and by-product water are removed under a gauge pressure of -0.09 MPa to obtain this special high-grade fluorosilicone oil with multidentate chelating sites and co-sulfidation sites - salicylaldehyde imine vinyl fluorosilicone oil.
[0011] 2. Compound supramolecular complex high-efficiency thermo-oxidative stabilizer: Made from industrial-grade cerium dioxide (CeO2, purity ≥99.5%, D 50 It is a mixture of 1.0-2.0 μm, industrial grade iron oxide red (Fe2O3, 1000 mesh), and multi-chelated supramolecular modified active magnesium oxide in a mass ratio of (1.5-3.0):(1.0-2.0):(1.0-2.5).
[0012] The preparation method of the multi-chelated supramolecular modified active magnesium oxide is as follows: Industrial-grade high-activity magnesium oxide with an iodine uptake value ≥85 mg / g is selected as the matrix carrier and suspended in anhydrous ethanol. First, 3.0%–5.0% (by mass) of industrial-grade plant tannic acid (a polyphenol complexing agent rich in catechol / pyrophenol structure) is added, and the mixture is stirred at 35°C for 1.5 hours to allow the tannic acid to be firmly chemically adsorbed and coated on the magnesium oxide surface. Subsequently, 2.0%–3.5% (by mass) of cerium acetylacetone (Ce(acac)3, commercially available) and 1.5%–2.5% (by mass) of iron acetylacetone (Fe(acac)3, commercially available) are added to the system, and the complexation reaction is continued at 50°C for 3 hours. Finally, the mixture is filtered, vacuum dried at 80°C, and ultrafinely pulverized to a median particle size D. 50 The resulting multi-chelated supramolecular modified active magnesium oxide has a thickness of 1.5–2.5 μm. A highly stable polyphenol-metal multidentate supramolecular coordination protective shell is formed on its surface.
[0013] Furthermore, a method for preparing a high heat-resistant oxidized fluorosilicone rubber material includes the following steps: Step 1: Plasticizing stage: Adjust the roll gap of the two-roll mill to 0.5-1.0 mm, and circulate cooling water through the rolls to maintain the temperature at 30-40℃. Add 100 parts of fluorosilicone raw rubber to the mill and fully enclose the rolls, then beat the rolls 3-5 times to ensure the raw rubber is fully plasticized.
[0014] Step 2: Mixing Stage (Adding Fillers and Special Chelating Structure Control Agents): Increase the roller gap to 1.5–2.0 mm, and add the pre-weighed hydrophobic fumed silica and salicylaldehyde imine vinyl fluorosilicone oil evenly in 3–4 batches, mixing thoroughly after each addition. Utilize the terminal hydroxyl groups to wet the silanol groups on the surface of the fumed silica. After the powder absorption is complete, keep the rubber compound surface smooth and free of powder.
[0015] Step 3: Stabilizer Addition Stage: Add the weighed compounded supramolecular complex high-efficiency thermo-oxidative stabilizer to the rubber compound from Step 2. After uniform mixing, pass through a thin pass 4-6 times. During this stage, under the shearing force of the two rollers, the "salicylaldehyde imine" multidentate ligand of the salicylaldehyde imine-based vinyl fluorosilicone oil side chain will undergo in-situ coordination exchange and supramolecular network interlocking with the tannic acid-cerium / iron centers exposed on the surface layer of the modified magnesium oxide, firmly anchoring the thermo-oxidative stabilizer molecular chain.
[0016] Step 4: Vulcanizing agent addition stage: Finally, add 50% of the bis(2,5) vulcanizing agent paste to the rubber compound, mix evenly, cut with left and right cutters 3 times each, beat with a triangular belt 5 times, and finally pass through the thin sheet 3 times. Cut the sheet and control the thickness of the rubber sheet to 2-3 mm.
[0017] Step 5: Resting and two-stage vulcanization: The unfinished rubber compound is rested for 12 to 24 hours under standard conditions (23±2℃).
[0018] Step 6: First-stage vulcanization: Place the compounded rubber in a mold and press it into shape using a flat vulcanizing machine at 165–175°C, with a pressure of 10–15 MPa and a time of 12–15 minutes. During this process, the vinyl side chains of the raw rubber and the vinyl side chains of the special fluorosilicone oil undergo co-vulcanization and covalent crosslinking under free radical initiation.
[0019] Step 7: Two-stage vulcanization: Place the sample in a hot air circulating oven for post-process vulcanization: maintain at 100°C for 1 hour, then raise the temperature to 200°C within 30 minutes and maintain for 4 hours to remove small molecule volatiles and promote the supramolecular multidentate coordination bond network to tend to the thermodynamically most stable state.
[0020] The beneficial effects of this invention are: This invention provides a high-heat-resistant oxidative fluorosilicone rubber material and its preparation method. Through the synergistic ratio and process of salicylaldehyde imine-based vinyl fluorosilicone oil and a compounded supramolecular complexing high-efficiency thermo-oxidative stabilizer, a dual-network interlocking structure of covalent crosslinking and dynamic reversible coordination crosslinking is successfully constructed within the rubber matrix. Based on the macroscopic detection data in Table 1, this invention exhibits the following technical effects and mechanisms compared to existing technologies: 1. Significantly improves the processing safety of uncured rubber and greatly extends scorch time: Based on the data in Table 1, the scorch time t of Comparative Example 2 (magnesium oxide without tannin polyphenol shell modification, directly mechanically mixed) at 120℃ is... 10 The scorch time is extremely short, only 4.2 minutes, posing a very high risk of early dead rubber in actual industrial continuous mixing or extrusion processing. This is because the strongly alkaline sites on the surface of the highly active magnesium oxide are directly exposed in the rubber compound, effectively catalyzing and accelerating the early decomposition of peroxide bonds in the peroxide vulcanizing agent (bis(2,5-dioxanone)) during the heating stage, releasing a large number of free radicals. Comparative Example 4, due to the imbalance in the mass ratio of internal inorganic components, also has a scorch time of only 6.5 minutes.
[0021] In contrast, the scorching time t at 120°C in Examples 1-3 of the present invention 10 The time was stably extended to 11.5–12.5 min (11.8 min in Example 1). Analysis of this data confirms that the present invention, by pre-adsorbing and encapsulating a plant tannic acid-metal (cerium / iron) supramolecular coordination network shell on the surface of active magnesium oxide, acts as a highly efficient physicochemical barrier during room temperature and low-temperature mixing processes, passivating the surface activity of magnesium oxide and thus providing excellent anti-scorching safety during processing.
[0022] 2. Significantly improved the original strength and toughness of the material, especially the macroscopic tear resistance: In evaluating the original tear strength index of the dynamic seal cracking evolution law, the original tear strength of Comparative Example 1 (degraded to ordinary fluorosilicone oil without salicylaldehyde imine group and standard KH-570 single-modified active magnesium oxide) was only 31.5 N / mm; Comparative Example 2, due to the lack of surface interface layer buffer, caused inorganic rigid particles to easily aggregate in a disordered manner, and its original tear strength dropped to the lowest of 20.5 N / mm.
[0023] In contrast, Examples 1, 2, and 3 of this invention show that the original tear strengths are increased to 44.5 N / mm, 41.2 N / mm, and 46.8 N / mm, respectively. This significant improvement in mechanical properties indicates that when salicylaldehyde-imine-based special fluorosilicone oil and polyphenol-metal co-coordinated modified active magnesium oxide are simultaneously introduced, a dynamic and reversible metal coordination network is successfully constructed within the rubber matrix. When the crescent-shaped cut sample is subjected to external macroscopic continuous tearing shear force, these low-energy supramolecular coordination bonds preferentially undergo reversible ring-opening fracture as "sacrificial bonds," converting the concentrated strain energy into micro-network deformation energy through chain segment sliding, thereby effectively preventing the propagation of macroscopic microcracks and tearing failure.
[0024] 3. Possesses excellent long-term resistance to heat and oxygen aging and extremely low compressive permanent deformation: After undergoing long-term ultra-high temperature accelerated hot air aging at 200℃ for 40 days, the hardness of Comparative Example 2 and Comparative Example 4 increased dramatically by 7 and 6 degrees, respectively, indicating severe hardening and brittleness. Their tensile strength retention (68%, 66%) and elongation at break retention (62%, 58%) significantly degraded. More critically, the compression set ε of Comparative Example 4 climbed to 34% (corresponding to a deformation retention rate of only 0.66), indicating that due to an imbalance in the inorganic component ratio (excessive iron oxide red and severe deficiency of cerium dioxide and modified magnesium oxide, which have acid-trapping and free radical-scavenging functions), defects were generated within the supramolecular network, making it unable to effectively prevent the degradation of the fluorosilicone rubber backbone under long-term thermo-oxidative conditions.
[0025] In contrast, Examples 1-3 of this invention exhibit extremely high thermo-oxidative stability, with hardness changes of only +1 to +2 degrees and tensile strength retention maintained at a high level of 92% to 95%. In particular, the compression set ε of Example 1 was reduced to a minimum of 14% (deformation retention rate of 0.86). This demonstrates that under the two-stage post-vulcanization setting, the extremely strong free radical scavenging ability of the tannic acid polyphenol shell and the spatially confined acid-trapping efficiency of the highly active MgO inside the supramolecular layer (efficiently locking the trace amounts of hydrofluoric acid HF gas generated by the thermal degradation of the main chain) achieve a balance in spatial configuration, effectively inhibiting the acid-catalyzed "backbiting" depolymerization reaction of the polysiloxane main chain, allowing the rubber to maintain a high level of elastic recovery energy under long-term pressure.
[0026] 4. It achieves excellent resistance to media extraction loss and long-term structural stability: After prolonged and intense immersion in high-temperature aviation fuel at 150℃ for 168 hours and subsequent vacuum drying at 100℃, Comparative Example 1 showed an extraction mass loss rate as high as -3.85%, and the hardness of the dried rubber skeleton increased dramatically by 12 degrees. Comparative Example 2, lacking polyphenol pre-complex coating, and Comparative Example 3, using ordinary fluorosilicone oil, also experienced net mass losses of -5.20% and -2.90%, respectively, with drying hardness deteriorating by 18 and 10 degrees, respectively. This data chain of mass loss and hardness embrittlement clearly reveals that conventional small-molecule structure control agents and metal stabilizers dispersed solely by physical adsorption are easily extracted, dissolved, and lost under long-term penetration of high-temperature fuel media, leading to drying shrinkage, hardening, and volume deformation within the rubber during mid-service.
[0027] In contrast, Examples 1-3 of this invention successfully suppressed the extraction mass loss rate to an extremely low level (only between -0.10% and -0.15%), and the hardness change after extraction and drying was only slightly adjusted by 2-3 degrees, with excellent volume stability and mechanical network structure. This property clearly demonstrates the deep causal relationship of the dual-network construction of this invention: the multidentate salicylaldehyde imine group of the special fluorosilicone oil side chain undergoes in-situ complexation and locking with the tannic acid-metal center on the modified magnesium oxide surface; simultaneously, the fluorosilicone oil, through its active unsaturated vinyl groups on its side chain, directly participates in the co-vulcanization reaction with raw rubber during a vulcanization stage, thereby using chemical bonds to "anchor" the polyphenol free radical scavenger, transition metal ions, and acid scavenger to the fluorosilicone rubber macromolecular network. The strong fuel medium cannot break this interlocking network, and the additive loss pathway is significantly suppressed.
[0028] In summary, Example 1, as the parameter ratio of the technical solution, while ensuring safe processing time (11.8 min), pushed the original tear strength to a high point of 44.5 N / mm. Furthermore, after continuous pressurized thermo-oxidative aging and long-term extraction of the oil medium, it exhibited a high level of physical and mechanical property retention and anti-extraction volume stability. The data changes in Table 1 confirm that the absence of single-agent modification (Comparative Example 3) or the removal of the supramolecular encapsulation structure (Comparative Example 2) both lead to a comprehensive deterioration of all core indicators, strongly demonstrating the practical value of the dual-network cross-linking interlocking technology of this invention. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Furthermore, unless otherwise specified, the raw materials, reagents, or devices used in the following embodiments can be obtained from conventional commercial channels or by existing known methods. Example 1
[0030] The high heat-resistant oxidizing fluorosilicone rubber material in this embodiment is prepared from the following raw materials: Fluorosilicone raw rubber (brand name FSE7560) 1000 g; Hydrophobic fumed silica (Aerosil R972) 300 g; Salicylaldehyde imine vinyl fluorosilicone oil 45 g; 55 g of compound supramolecular complex high-efficiency thermo-oxidative stabilizer (made by uniformly mixing 25 g of industrial grade cerium dioxide, 15 g of industrial grade iron oxide red, and 15 g of multi-chelated supramolecular modified active magnesium oxide); 10 g of 50% (by mass) bis(2,5) sulfide paste.
[0031] The specific preparation process steps are as follows: (I) Preparation of key raw materials: Preparation of salicylaldehyde imine vinyl fluorosilicone oil: Weigh 44.1 g of aminopropyl vinyl fluorosilicone oil (molecular weight 3800, kinematic viscosity 500 mPa·s, terminal hydroxyl mass fraction 4.5%, side chain unsaturated vinyl mass fraction 1.8%, side chain aminopropyl mass fraction 1.2%) and 0.9 g of anhydrous salicylaldehyde (amino to aldehyde group equimolar ratio), and dissolve them in 100 mL of anhydrous ethanol. The condensation reaction was carried out at 45 °C with stirring for 3.5 hours. Subsequently, the ethanol solvent and byproduct water were removed under a gauge pressure of -0.09 MPa to obtain 45 g of salicylaldehyde imine vinyl fluorosilicone oil (of which the mass fraction of the side chain salicylaldehyde imine functional group was 2.5%).
[0032] Preparation of multi-chelated supramolecular modified active magnesium oxide: 14.2 g of industrial-grade highly active magnesium oxide with an iodine uptake value of 90 mg / g was selected as the matrix carrier and suspended in 150 mL of anhydrous ethanol. 0.57 g of industrial-grade plant tannic acid (accounting for 4.0% of the mass of active magnesium oxide) was added, and the mixture was stirred at 35 °C for 1.5 hours to allow the tannic acid to chemically adsorb and coat the surface of the active magnesium oxide. Subsequently, 0.40 g of cerium acetylacetone (accounting for 2.8% of the mass of active magnesium oxide) and 0.28 g of iron acetylacetone (accounting for 2.0% of the mass of active magnesium oxide) were added to the system, and the complexation reaction was continued at 50 °C for 3 hours. Finally, the mixture was filtered, vacuum dried at 80 °C, and ultrafine pulverized to a median particle size D50 of 2.0 μm to obtain 15 g of multi-component chelated supramolecular modified active magnesium oxide.
[0033] Preparation of compound supramolecular complex high-efficiency thermo-oxidative stabilizers: 25 g of industrial-grade cerium dioxide, 15 g of industrial-grade iron oxide red, and 15 g of the multi-component chelated supramolecular modified active magnesium oxide prepared above were physically and uniformly mixed to obtain 55 g of compound supramolecular complexed high-efficiency thermo-oxidative stabilizer.
[0034] (II) Preparation of fluorosilicone rubber materials: Raw rubber plasticizing: Start the two-roll mill, introduce cooling water to strictly control the surface temperature of the rolls at 35℃, and adjust the gap between the two rolls (roll distance) to 0.8 mm. Add 1000 g of fluorosilicone raw rubber to the mill. After the rubber compound has fully coated the rolls, perform a V-belt operation 5 times in a row to ensure that the raw rubber macromolecular chains are fully subjected to mechanical shearing and plasticized uniformly.
[0035] Mixing and Surface Modification: The roll gap of the open mill was increased to 1.8 mm. 300 g of hydrophobic fumed silica was premixed with 45 g of the salicylaldehyde imine vinyl fluorosilicone oil prepared above. This mixture was then added evenly to the raw rubber wrapped around the rolls in four separate additions. After each addition, the powder was absorbed and the rubber surface was smooth and free of powder before adding the next batch. After all additions were completed, the left and right cutters were used three times each to ensure that the terminal hydroxyl groups of the structure control agent and the silanol groups on the surface of the silica under the shearing heat generated by the rolls under sufficient condensation reaction.
[0036] In-situ coordination complexation: Maintaining a roll gap of 1.8 mm, add 55 g of the prepared supramolecular complex high-efficiency thermo-oxidative stabilizer to the compound in one go. Perform a re-mixing operation, then reduce the roll gap to 0.5 mm and perform a thin-pass triangular belt operation 6 times. During this process, the strong mechanical shear force promotes in-situ coordination exchange between the salicylaldehyde imine groups of the fluorosilicone oil side chain and the tannic acid-cerium / iron centers on the modified magnesium oxide surface, constructing a supramolecular network.
[0037] Vulcanization integration: Increase the roller gap to 2.0 mm and evenly add 10 g of 50% (w / w) bis(2,5)-pentachloride paste. After uniform mixing, operate the cutter to make cross cuts 3 times on each side, followed by 5 V-belt cuts. Finally, adjust the roller gap to 2.5 mm and sheet the product to obtain an unvulcanized fluorosilicone compound sheet with a thickness of 2.5 mm.
[0038] Parking and two-stage vulcanization: After the rubber is cut, the compounded rubber sheet is placed in a standard laboratory environment with a temperature of 23°C and a relative humidity of 50% for 18 hours to fully eliminate the internal stress generated during the compounding process.
[0039] First-stage flat vulcanization: After the rubber compound has been left to stand, it is cut and placed into a standard metal mold, then transferred into a flat vulcanizing machine. The vulcanization temperature is set to 170℃, the molding pressure is applied to 12 MPa, and the mixture is continuously heated and pressed for 12 minutes. The sample is then demolded to obtain the primary vulcanized rubber sample.
[0040] Two-stage post-curing: The rubber sample after the first stage of curing is suspended in an oven with hot air circulation for secondary cross-linking. Temperature control program is initiated: First, the sample is held at 100°C for 1 hour. Then, the temperature controller is adjusted to linearly raise the oven temperature to 200°C within 30 minutes, and the sample is continuously baked at a constant temperature of 200°C for 4 hours. After baking, the sample is cooled to room temperature with the oven to obtain the final high-heat-resistant fluoropolymer silicone rubber material product of Example 1. Example 2
[0041] The high heat-resistant oxidizing fluorosilicone rubber material in this embodiment is prepared from the following raw materials: Fluorosilicone raw rubber (brand name FSE7560) 1000 g; Hydrophobic fumed silica (Aerosil R972) 250 g; Salicylaldehyde imine vinyl fluorosilicone oil 30 g; 35 g of compound supramolecular complex high-efficiency thermo-oxidative stabilizer (made by uniformly mixing 15 g of industrial grade cerium dioxide, 10 g of industrial grade iron oxide red, and 10 g of multi-chelated supramolecular modified active magnesium oxide); 8 g of bis(2,5) sulfide paste with a mass fraction of 50%.
[0042] The specific preparation process steps are as follows: (I) Preparation of key raw materials: Preparation of salicylaldehyde imine vinyl fluorosilicone oil: 29.5 g of aminopropyl vinyl fluorosilicone oil (molecular weight 3200, kinematic viscosity 420 mPa·s, terminal hydroxyl mass fraction 5.2%, side chain unsaturated vinyl mass fraction 1.2%, side chain aminopropyl mass fraction 0.9%) and 0.5 g of anhydrous salicylaldehyde (equal molar ratio of amino to aldehyde groups) were weighed and dissolved in 80 mL of anhydrous ethanol. The condensation reaction was carried out by stirring at 40 °C for 4 hours, followed by removal of ethanol solvent and byproduct water under a gauge pressure of -0.09 MPa to obtain 30 g of salicylaldehyde imine vinyl fluorosilicone oil (of which the mass fraction of the side chain salicylaldehyde imine functional group was 1.8%).
[0043] Preparation of multi-chelated supramolecular modified active magnesium oxide: 9.5 g of industrial-grade highly active magnesium oxide with an iodine uptake value of 85 mg / g was selected as the matrix carrier and suspended in 100 mL of anhydrous ethanol. 0.285 g of industrial-grade plant tannic acid (3.0% of the active magnesium oxide mass) was added, and the mixture was stirred at 35 °C for 1.5 hours to allow the tannic acid to chemically adsorb and coat the surface of the active magnesium oxide. Subsequently, 0.19 g of cerium acetylacetone (2.0% of the active magnesium oxide mass) and 0.14 g of iron acetylacetone (1.5% of the active magnesium oxide mass) were added to the system in synergistic reaction. The complexation reaction was continued at 50 °C for 3 hours. Finally, the mixture was filtered, vacuum dried at 80 °C, and ultrafine pulverized to a median particle size D50 of 1.5 μm to obtain 10 g of multi-component chelated supramolecular modified active magnesium oxide.
[0044] Preparation of compound supramolecular complex high-efficiency thermo-oxidative stabilizers: 15 g of industrial-grade cerium dioxide, 10 g of industrial-grade iron oxide red, and 10 g of the multi-component chelated supramolecular modified active magnesium oxide prepared above were physically and uniformly mixed to obtain 35 g of compound supramolecular complexed high-efficiency thermo-oxidative stabilizer.
[0045] (II) Preparation of fluorosilicone rubber materials: Raw rubber plasticizing: Start the two-roll mill, circulate cooling water through the rolls to maintain the surface temperature at 30°C, and adjust the initial roll gap to 0.5 mm. Add 1000 g of fluorosilicone raw rubber into the mill, wrap it around the rolls, and continuously beat the V-belt three times to achieve preliminary shear plasticizing of the raw rubber at a low roll gap.
[0046] Mixing and Surface Modification: Adjust the roll gap of the open mill to 1.5 mm. Mix 250 g of hydrophobic fumed silica with the 30 g of salicylaldehyde imine vinyl fluorosilicone oil prepared above, and then gradually and evenly add the mixture to the raw rubber in three portions. After each addition, the mixture must be kneaded until the surface of the rubber compound is smooth and free of free fumed silica powder. After the addition is complete, make three cuts on each side with the left and right cutting tools.
[0047] In-situ coordination complexation: Maintaining the roll gap at 1.5 mm, add 35 g of the above-prepared compounded supramolecular complex high-efficiency thermo-oxidative stabilizer to the open mill. After several up-and-down tumbling cycles, tighten the roll gap to 0.5 mm and perform continuous thin-pass triangular belt operation on the rubber compound 4 times. Relying on strong shearing, the metal oxide aggregates are broken, achieving microscopic uniform dispersion and promoting the self-assembly and interlocking of coordination bonds.
[0048] Vulcanization integration: Widen the open mill roll gap to 1.8 mm, and evenly knead 8 g of 50% (by mass) bis(2,5)-pentachloride paste into the rubber compound. Cut the rubber three times on each side and beat the V-belt five times. Finally, fix the open mill roll gap at 2.0 mm and sheet the rubber to obtain a compounded rubber sheet with a thickness of 2.0 mm.
[0049] Parking and two-stage vulcanization: Let the raw rubber sheet stand at 25°C for 24 hours.
[0050] First-stage flat vulcanization: Place the settled rubber sheet in the mold and send it into the flat vulcanizing machine. Set the flat plate temperature to 165℃, adjust the clamping pressure to 10 MPa, and continuously press and vulcanize for 15 minutes before quickly opening the mold and removing the sample.
[0051] Two-stage post-curing: The first sample was transferred into a hot air circulating oven. Temperature was controlled according to the program: constant temperature at 100℃ for 1 hour; then slowly increased to 200℃ over 30 minutes; finally, continuous air crosslinking and curing at 200℃ for 4 hours was performed. After the curing period, the sample was removed and allowed to cool naturally in air to obtain the high heat-resistant fluoropolymer rubber material product of Example 2. Example 3
[0052] The high heat-resistant oxidizing fluorosilicone rubber material in this embodiment is prepared from the following raw materials: Fluorosilicone raw rubber (brand name FSE7560) 1000 g; Hydrophobic fumed silica (Aerosil R972) 350 g; Salicylaldehyde imine vinyl fluorosilicone oil 60 g; 75 g of compound supramolecular complex high-efficiency thermo-oxidative stabilizer (composed of 35 g of industrial grade cerium dioxide, 20 g of industrial grade iron oxide red, and 20 g of multi-chelated supramolecular modified active magnesium oxide uniformly mixed); 15 g of bis(2,5)-5-sulfurizing agent paste with a mass fraction of 50%.
[0053] The specific preparation process steps are as follows: (I) Preparation of key raw materials: Preparation of salicylaldehyde imine vinyl fluorosilicone oil: Weigh 58.8 g of aminopropyl vinyl fluorosilicone oil (molecular weight 4400, kinematic viscosity 580 mPa·s, terminal hydroxyl mass fraction 3.8%, side chain unsaturated vinyl mass fraction 2.2%, side chain aminopropyl mass fraction 1.5%) and 1.2 g of anhydrous salicylaldehyde (amino to aldehyde group equimolar ratio), and dissolve them in 150 mL of anhydrous ethanol. The condensation reaction was carried out at 50 °C with stirring for 3 hours. Subsequently, the ethanol solvent and byproduct water were removed under a gauge pressure of -0.09 MPa to obtain 60 g of salicylaldehyde imine vinyl fluorosilicone oil (of which the mass fraction of the side chain salicylaldehyde imine functional group was 3.2%).
[0054] Preparation of multi-chelated supramolecular modified active magnesium oxide: 18.6 g of industrial-grade highly active magnesium oxide with an iodine uptake value of 95 mg / g was selected as the matrix carrier and suspended in 200 mL of anhydrous ethanol. 0.93 g of industrial-grade plant tannic acid (accounting for 5.0% of the mass of active magnesium oxide) was added, and the mixture was stirred at 35 °C for 1.5 hours to allow the tannic acid to chemically adsorb and coat the surface of the active magnesium oxide. Subsequently, 0.65 g of cerium acetylacetone (accounting for 3.5% of the mass of active magnesium oxide) and 0.47 g of iron acetylacetone (accounting for 2.5% of the mass of active magnesium oxide) were added to the system, and the complexation reaction was continued at 50 °C for 3 hours. Finally, the mixture was filtered, vacuum dried at 80 °C, and ultrafine pulverized to a median particle size D50 of 2.5 μm to obtain 20 g of multi-component chelated supramolecular modified active magnesium oxide.
[0055] Preparation of compound supramolecular complex high-efficiency thermo-oxidative stabilizers: 35 g of industrial-grade cerium dioxide, 20 g of industrial-grade iron oxide red, and 20 g of the multi-component chelated supramolecular modified active magnesium oxide prepared above were physically and uniformly mixed to obtain 75 g of compound supramolecular complexed high-efficiency thermo-oxidative stabilizer.
[0056] (II) Preparation of fluorosilicone rubber materials: Raw rubber plasticizing: Start the two-roll mill, adjust the roller cooling water valves to maintain the surface temperature at 40℃, and adjust the roller gap to 1.0 mm. Add 1000 g of fluorosilicone raw rubber, and after fully coating the rollers, perform a rapid V-belt operation 5 times.
[0057] Mixing and Surface Modification: Adjust the roll gap of the open mill to 2.0 mm. Premix 350 g of hydrophobic fumed silica with the 60 g of salicylaldehyde imine vinyl fluorosilicone oil prepared above, and add it to the raw rubber wrapped around the rolls in multiple batches (4 times) at a slow speed. Each time, thoroughly mix until the high-hardness silica is completely absorbed into the fluorosilicone matrix and the surface is smooth. After feeding, perform 4 cuts on each side.
[0058] In-situ coordination complexation: At a roller gap of 2.0 mm, 75 g of the above-prepared compounded supramolecular complex high-efficiency thermo-oxidative stabilizer powder was added to the rubber compound and mixed evenly. Subsequently, the roller gap was precisely adjusted to 0.6 mm, and the entire rubber compound was subjected to a high-strain shear thin-pass operation 6 times to force the salicylaldehyde imine groups and tannic acid metal complexes to coordinate in situ in a dense network.
[0059] Vulcanization integration: Widen the roll gap to 2.2 mm and add 15 g of 50% (w / w) bis(2,5) vulcanizing agent paste. After mixing until no visible lumps of vulcanizing agent remain, cut the mixture three times on each side and beat it with a V-belt five times. Finally, adjust the roll gap of the open mill to 3.0 mm and sheet it into a homogeneous compound rubber sheet with a thickness of 3.0 mm.
[0060] Parking and two-stage vulcanization: Place the compounded rubber sheet in an environment of 22°C for a standard 12-hour parking period to release stress.
[0061] First-stage flat vulcanization: Place the film in a standard cylindrical mold (Φ13 mm × 6.3 mm) and a dumbbell-shaped mold. Transfer it to a flat vulcanizing machine, set the vulcanization temperature to 175℃, adjust the molding pressure to 15 MPa, and remove it from the mold after 12 minutes of flat vulcanization.
[0062] Two-stage post-curing process: The demolded sample is pushed into a hot air circulating post-curing oven. Temperature control is activated: First, the temperature is maintained at 100°C for 1 hour to expel trace amounts of volatiles; then, the temperature is uniformly increased to 200°C over 30 minutes; and baked at a constant temperature of 200°C for 4 hours to complete the final thermodynamic shaping of the supramolecular network. After cooling in the oven, the high heat-resistant fluoropolymer rubber material of Example 3 is obtained.
[0063] Comparative Example 1 Comparative Example 1 served as the control group for Example 1: Setup method (control variables): Keep the amount and specifications of the fluorosilicone raw rubber (1000 g), hydrophobic fumed silica (300 g), inorganic cerium dioxide (25 g), inorganic iron oxide red (15 g), and 50% by mass of bis(2,5-diphenyl)sulfurizing agent paste (10 g) consistent with those in Example 1.
[0064] The variables that were changed were: 45 g of "salicylaldehyde imine-based vinyl fluorosilicone oil" was replaced with 45 g of conventional hydroxyl vinyl fluorosilicone oil (commercially available common oligomer) that does not contain salicylaldehyde imine groups; and 15 g of "multi-chelate supramolecular modified active magnesium oxide" was replaced with 15 g of commercially available common active magnesium oxide modified with KH-570 silane coupling agent.
[0065] Preparation process: Same as in Example 1.
[0066] Comparative Example 2 Comparative Example 2 served as the control group for Example 1: Setting method (control variables): Keep the amount and specifications of all raw materials used in Example 1 consistent (including the pure mass of each component of fluorosilicone oil and stabilizer).
[0067] The changed variable: When preparing the inorganic thermo-oxidative stabilizer, plant tannins were not used to pre-suspend and coat magnesium oxide. Instead, commercially available high-activity magnesium oxide (15 g), anhydrous and grease-free cerium acetylacetone (converted by equivalent metal element mass), and ferric acetylacetone (converted by equivalent metal element mass) were directly and roughly mechanically mixed with cerium dioxide and iron oxide red and fed into a two-roll mill.
[0068] Preparation process: Same as in Example 1.
[0069] Comparative Example 3 Comparative Example 3 served as the control group for Example 1: Setup method (control variables): Keep the amount and specifications of raw rubber, silica, compound supramolecular complex high-efficiency thermo-oxidative stabilizer (55 g, containing 15 g of pre-prepared multi-component chelated supramolecular modified magnesium oxide) and vulcanizing agent consistent with those in Example 1.
[0070] The variable that was changed was to replace 45 g of special fluorosilicone oil with salicylaldehyde imine polydentate ligands with 45 g of ordinary low-molecular-weight fluorosilicone oil with the same molecular weight (3500), the same content of terminal hydroxyl groups and side chain vinyl groups, but without salicylaldehyde imine functional groups.
[0071] Preparation process: Same as in Example 1.
[0072] Comparative Example 4 Comparative Example 4 served as the control group for Example 1: Setting method (control variables): Keep the amounts of raw rubber, fumed silica, special chelated fluorosilicone oil and vulcanizing agent consistent as in Example 1, and keep the total amount of compound stabilizer added at 55 g.
[0073] The changed variable: The mass ratio of the three components within the inorganic compound stabilizer was significantly altered. The mass ratio (CeO2:Fe2O3:supramolecular modified MgO = 1.66:1:1) in Example 1, which conformed to the limitations of this invention, was adjusted to: 10g of industrial-grade cerium dioxide, 35g of industrial-grade iron oxide red, and 10g of pre-prepared multi-component chelated supramolecular modified active magnesium oxide (at this point, the mass ratio of the three components becomes 1:3.5:1, with excessive iron oxide red and insufficient other components, deviating from the limits of this invention).
[0074] Preparation process: Same as in Example 1.
[0075] Test Example 1 Performance tests were conducted on Examples 1 to 3 and Comparative Examples 1 to 4. The test process is as follows, and the test results are shown in Table 1. (1) Processing scorch performance test: conducted according to GB / T 1232.1-2000. The test temperature was 120℃, and the scorch time t corresponding to the rotor Moni value rising by 10 Moni units from the lowest point was recorded. 10 (min).
[0076] (2) Test of original tensile strength and elongation at break: The hardness was determined according to GB / T 531.1-2008 Shore A hardness; the tensile properties were tested according to GB / T 528-2009 using dumbbell-shaped type 2 specimens, and the original tensile strength (MPa) and elongation at break (%) were tested on a tensile testing machine at a speed of 500 mm / min.
[0077] (3) Macroscopic tear strength test: conducted in accordance with GB / T 529-2008. A crescent-shaped specimen (with a standard pre-cut) was used and continuously stretched at 500 mm / min on an electronic tensile testing machine until complete fracture. The maximum load was automatically recorded and converted into the original tear strength (N / mm).
[0078] (4) 200℃×40d long-cycle hot air accelerated aging test: carried out in accordance with GB / T 3512-2014. The standard tensile specimen and crescent tear specimen were suspended in a 200℃ oven for continuous thermo-oxidative aging for 40 days (40 d). After being taken out and conditioned at standard room temperature for 16 hours, the tensile strength retention rate (%), elongation at break retention rate (%) and tear resistance (N / mm) after aging were measured.
[0079] (5) High-temperature compression long-term deformation and retention rate test: conducted according to GB / T 7759.1-2015. The sample was a Φ13 mm × 6.3 mm cylinder with a fixed compression ratio of 25%. The entire locking device was placed in an aging chamber at 200℃ and subjected to continuous compression aging for 40 days (40 d). After the expiration, the clamp was quickly released under hot conditions, and after 30 min of free recovery, the recovery height was measured, the compression permanent deformation ε (%) was calculated, and the compression permanent deformation retention rate (1-ε) was calculated accordingly.
[0080] (6) High-temperature aviation fuel long-term "immersion extraction loss" test: The test was conducted according to GB / T 1690-2010 "Test Method for Liquid Resistance of Vulcanized Rubber or Thermoplastic Rubber". The weighed vulcanized rubber sample was completely immersed in No. 3 standard aviation fuel (Jet A-1 simulated medium) and continuously immersed and extracted at high temperature in a sealed pressure tank at 150°C for 168 hours (168 h, up to 7 days). After the expiration, the sample was removed and dried in a vacuum oven at 100°C to constant weight (to remove adsorbed volatile fuel components).
[0081] A. Calculate the extraction mass loss rate (%): The closer the mass loss is to 0, the stronger the resistance of the additives and stabilizers inside the rubber to extraction loss. B. Subsequently, the change in hardness (degrees) after extraction and aging was measured: If a large amount of rubber additives are extracted, the rubber will shrink and harden drastically after drying, and the hardness value will soar.
[0082] Table 1 Test Results
[0083] Analysis of the data in Table 1: By systematically comparing the data of Examples 1-3 with Comparative Examples 1-4 in terms of various macroscopic physical, chemical, and processing rheological properties, the modification effects and synergistic effects of each component can be analyzed in depth from the perspective of rubber macromolecular network construction and multiphase interface crosslinking mechanism: 1. Analysis of scorch characteristics during processing of rubber compound (verification of the room-temperature isolation and passivation effect of the supramolecular shell): From the processing characteristics of the uncured rubber in Table 1, the scorch time t of Comparative Example 2 (without tannic acid polyphenol shell modification, directly mechanically mixed with metal salt and active magnesium oxide) at 120°C is... 10With a scorch time of only 4.2 min, there is an extremely high risk of early localized vulcanization (dead rubber) in actual continuous extrusion or compounding processes. This is because the strongly alkaline sites on the surface of conventional active magnesium oxide are directly exposed in the rubber compound, which effectively catalyzes and accelerates the early decomposition of peroxide bonds in the peroxide vulcanizing agent (bis(2,5-dioxanone)) during the heated compounding stage, releasing a large number of free radicals. In contrast, Comparative Example 4, due to the imbalance in the proportion of internal inorganic composite stabilizers (severe excess of iron oxide red and insufficient modified magnesium oxide), also had a scorch time of only 6.5 min.
[0084] In contrast, the scorching time t at 120°C in Examples 1-3 of the present invention 10 The stable duration was extended to 11.5–12.5 min (11.8 min in Example 1). This fundamental reversal in rheological data directly corresponds to the interfacial reaction design in step 3: the surface of the active magnesium oxide was pre-adsorbed and coated with a dense plant tannic acid-metal (cerium / iron) supramolecular coordination network shell before mixing. This shell acts as a highly efficient physicochemical barrier during room temperature and low-temperature mixing, passivating the surface activity of magnesium oxide and preventing its direct contact with the peroxide sulfiding agent, thereby providing excellent anti-scorching safety during processing.
[0085] 2. Original physical and mechanical properties and tear resistance analysis (verifying the stress dissipation mechanism of dynamic coordination bonds): In the core indicator evaluating the crack evolution of dynamic seals—macroscopic tear strength (original)—Comparative Example 1 (degraded to conventional fluorosilicone oil without salicylaldehyde imine groups and standard KH-570 single-modified active magnesium oxide) had an original tear strength of only 31.5 N / mm. Comparative Example 2, lacking a surface interface layer for buffering, experienced disordered self-aggregation of inorganic rigid particles under shear force, forming numerous stress concentration crack sources, resulting in an original tear strength as low as 20.5 N / mm.
[0086] In contrast, Examples 1, 2, and 3 of this invention show a significant leap in their original tear resistance, reaching 44.5 N / mm, 41.2 N / mm, and 46.8 N / mm, respectively. This leap in mechanical properties indicates that only when salicylaldehyde imine-based special fluorosilicone oil and polyphenol-metal co-coordinated modified active magnesium oxide are simultaneously introduced can a dual-network interlocking structure of covalent crosslinking and dynamic reversible metal coordination crosslinking be successfully constructed within the rubber matrix during the first vulcanization process in step 6. When the crescent-shaped cut sample is subjected to external macroscopic continuous tearing shear force, these supramolecular coordination bonds with lower bond energies act as "sacrificial bonds," preferentially undergoing reversible ring-opening fracture. Through chain segment sliding, the concentrated strain energy is converted into microscopic network deformation energy, thereby effectively preventing the propagation of macroscopic microcracks and tearing failure.
[0087] 3. Analysis of long-term thermo-oxidative aging and compressive deformation performance at 200°C for 40 days (verification of the spatial confinement anti-depolymerization mechanism): After undergoing long-term ultra-high temperature accelerated hot air aging at 200°C for 40 days, the hardness of Comparative Example 2 and Comparative Example 4 increased dramatically by 7 and 6 degrees, respectively, indicating significant hardening and embrittlement. Their tensile strength retention (68%, 66%) and elongation at break retention (62%, 58%) both showed substantial chemical degradation. Simultaneously, the compression set ε of Comparative Example 4 climbed to 34% (corresponding to a deformation retention rate of only 0.66). This indicates that due to the imbalanced mass ratio of inorganic components, excessive iron oxide red, and a severe deficiency of cerium dioxide and modified magnesium oxide (which have acid-trapping and free radical scavenging functions), severe lattice and coordination defects were generated within the supramolecular network, failing to effectively prevent the degradation of the fluorosilicone rubber backbone under long-term thermo-oxidative conditions.
[0088] In contrast, Examples 1-3 of this invention exhibit extremely high thermo-oxidative stability, with hardness changes of only +1 to +2 degrees and tensile strength retention maintained at a high specification of 92% to 95%. In particular, the compression set ε of Example 1 was reduced to a minimum of 14% (deformation retention rate of 0.86). This demonstrates that under the two-stage post-vulcanization setting in step 7, the extremely strong free radical scavenging ability of the tannic acid polyphenol shell and the spatially confined acid-trapping efficiency of the highly active MgO inside the supramolecular layer (efficiently locking the trace amounts of hydrofluoric acid HF gas generated by the thermal degradation of the main chain) achieve the best spatial configuration balance, blocking the acid-catalyzed "backbiting" depolymerization reaction of the polysiloxane main chain, so that the rubber still maintains excellent elastic recovery performance under long-term pressure.
[0089] 4.150°C×168h Long-term extraction performance analysis of fuel (verification of the dual-network anti-extraction loss effect): After prolonged and intense immersion in high-temperature fuel at 150°C for 168 hours, followed by vacuum drying at 100°C to absolute constant weight, Comparative Example 1 (conventional method) showed an extraction mass loss rate as high as -3.85%, and the hardness of the dried rubber skeleton increased dramatically by 12 degrees. Comparative Example 2, lacking polyphenol pre-complex coating, and Comparative Example 3, using ordinary fluorosilicone oil, also showed net mass losses of -5.20% and -2.90%, respectively, with drying hardness deteriorating by 18 and 10 degrees, respectively. This data chain of mass loss and hardness embrittlement clearly reveals the objective defects of existing technologies: conventional small-molecule structure control agents and metal stabilizers and antioxidants that rely solely on physical adsorption dispersion are easily extracted, dissolved, and lost in large quantities under long-term penetration of high-temperature fuel media, leading to a precipitous drying shrinkage, hardening, and volume deformation within the rubber during mid-service.
[0090] In contrast, Examples 1-3 of this invention successfully suppressed the extraction mass loss rate to an extremely low level (only between -0.10% and -0.15%), and the hardness change after extraction and drying was only slightly adjusted by 2-3 degrees, with the material's volume stability and mechanical network structure remaining intact. This effective macroscopic property leap clearly demonstrates the deep causal relationship of the dual-network construction of this invention: the multidentate salicylaldehyde imine group of the special fluorosilicone oil side chain undergoes strong in-situ complexation and locking with the tannic acid-metal center on the surface of modified magnesium oxide under mixing shear; simultaneously, the fluorosilicone oil, through its active unsaturated vinyl groups on its side chain, directly participates in the co-vulcanization reaction with raw rubber in the first stage of vulcanization in step 6, thereby using chemical bonds to "anchor" the polyphenol free radical scavenger, transition metal ions, and acid scavenger to the large network of fluorosilicone rubber macromolecules. The strong medium of fuel cannot break this interlocking network, and the pathway for additive loss is blocked.
[0091] 5. Summary: In summary, Example 1, as the optimal parameter ratio of the technical solution, ensures excellent processing safety operation time (11.8 min) while pushing the original tear strength to a high point of 44.5 N / mm. After continuous pressure thermo-oxidative aging and long-term extraction in harsh oil media, it exhibits a high level of physical and mechanical property retention rate and anti-extraction volume stability.
[0092] The macroscopic performance data in Table 1 form a tight logical loop in terms of causality: the absence of single-agent modification (Comparative Example 3) or the elimination of supramolecular encapsulation structures (Comparative Example 2) both lead to a comprehensive deterioration of all core indicators. This scientifically demonstrates that the cross-disciplinary introduction of coordination chemistry in this invention achieves comprehensive and leapfrog performance synergy in solving key defects of traditional high heat-resistant rubber materials, such as easy early scorching and dead rubber, easy extraction and loss of additives in the medium, and easy re-biting, depolymerization, hardening, and cracking under long-term thermal and oxygen pressure. It has extremely high industrial practical value.
[0093] It should be noted that, in this document, terms such as “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus.
[0094] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high heat-resistant oxidized fluorosilicone rubber material, characterized in that, Including the following parts by weight of raw materials: 100 parts of fluorosilicone raw rubber; 25-35 parts of hydrophobic fumed silica; 3-6 parts of salicylaldehyde imine vinyl fluorosilicone oil; 4-9 parts of a compound supramolecular complex high-efficiency thermo-oxidative stabilizer; 0.8 to 1.5 parts of a 50% by mass dichlorination agent paste.
2. The high heat-resistant oxidized fluorosilicone rubber material according to claim 1, characterized in that, The salicylaldehyde imine-based vinyl fluorosilicone oil has a molecular weight of 3000–4500, a kinematic viscosity of 400–600 mPa·s, a terminal hydroxyl mass fraction of 3.8%–5.2%, a side-chain unsaturated vinyl mass fraction of 1.2%–2.2%, and a side-chain salicylaldehyde imine functional group mass fraction of 1.8%–3.2%.
3. The high heat-resistant oxidized fluorosilicone rubber material according to claim 2, characterized in that, The preparation method of the salicylaldehyde imine vinyl fluorosilicone oil is as follows: side chain aminopropyl vinyl fluorosilicone oil and anhydrous salicylaldehyde are mixed in anhydrous ethanol at an equimolar ratio of amino to aldehyde groups, and the mixture is stirred and condensed at 40-50°C for 3-4 hours. Then, ethanol and byproduct water are removed under a gauge pressure of -0.09 MPa.
4. The high heat-resistant oxidized fluorosilicone rubber material according to claim 1, characterized in that, The compounded supramolecular complex high-efficiency thermo-oxidative stabilizer is uniformly compounded from industrial-grade cerium dioxide, industrial-grade iron oxide red, and multi-component chelated supramolecular modified active magnesium oxide in a mass ratio of (1.5-3.0):(1.0-2.0):(1.0-2.5); wherein the purity of the industrial-grade cerium dioxide is ≥99.5%, and the median particle size D50 is 1.0-2.0 μm; the fineness of the industrial-grade iron oxide red is 1000 mesh.
5. The high heat-resistant oxidized fluorosilicone rubber material according to claim 4, characterized in that, The preparation method of the multi-chelated supramolecular modified active magnesium oxide is as follows: industrial-grade high-activity magnesium oxide with an iodine uptake value ≥85 mg / g is selected as the matrix carrier and suspended in anhydrous ethanol. First, 3.0% to 5.0% of industrial-grade plant tannic acid is added to the matrix by mass fraction, and the mixture is stirred at 35°C for 1.5 hours to allow the tannic acid to be chemically adsorbed and coated on the surface of the active magnesium oxide. Then, 2.0% to 3.5% of cerium acetylacetone and 1.5% to 2.5% of iron acetylacetone by mass fraction are added to the system in synergistic reaction, and the complexation reaction is continued at 50°C for 3 hours. Finally, the mixture is filtered, vacuum dried at 80°C, and ultrafinely pulverized to a median particle size D50 of 1.5 to 2.5 μm.
6. A method for preparing a high heat-resistant oxidized fluorosilicone rubber material according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: Plasticizing stage: Add 100 parts of fluorosilicone raw rubber to a two-roll mill for plasticizing; Step 2: Mixing stage: Add the hydrophobic fumed silica and the salicylaldehyde imine vinyl fluorosilicone oil evenly to the plasticized rubber compound and mix evenly; Step 3: Stabilizer addition stage: Add the compounded supramolecular complex high-efficiency thermo-oxidative stabilizer to the mixed rubber compound, and then mix it evenly and pass it through a thin sheet. Step 4: Vulcanizing agent addition stage: Finally, add 50% by mass of the bis(2,5) vulcanizing agent paste to the rubber compound, mix evenly, and then sheet to obtain unvulcanized fluorosilicone compound rubber sheet. Step 5: Resting stage: After the uncured fluorosilicone compound film is cut, it is left to rest in a standard environment for 12 to 24 hours to eliminate internal stress; Step 6: First-stage vulcanization: Place the unvulcanized fluorosilicone compound rubber sheet after it has been left to stand in the mold, and use a flat vulcanizing machine to press and vulcanize it to obtain a primary vulcanized rubber sample. Step 7: Two-stage vulcanization: The primary vulcanized rubber sample is placed in a hot air circulating oven for post-vulcanization to obtain the high heat-resistant fluorosilicone rubber material.
7. The method for preparing a high heat-resistant oxidized fluorosilicone rubber material according to claim 6, characterized in that, In step 1, the roll gap of the two-roll mill is adjusted to 0.5-1.0 mm, and the rolls are cooled with cooling water to maintain the temperature at 30-40℃. After the rubber compound is fully coated on the rolls, it is continuously rolled in a V-belt 3-5 times. In step 2, the roll gap of the two-roll mill is increased and adjusted to 1.5-2.0 mm, and the pre-weighed hydrophobic fumed silica and salicylaldehyde imine vinyl fluorosilicone oil are added evenly in 3-4 portions.
8. The method for preparing a high heat-resistant oxidized fluorosilicone rubber material according to claim 6, characterized in that, In step 3, after the rolling is uniform, the roll gap is tightened to 0.5-0.6 mm and the thin pass is performed 4-6 times. In step 4, the roll gap of the open mill is adjusted to 1.8-2.2 mm, and after adding 50% of the bis(2,5) vulcanizing agent paste and mixing it uniformly, the left and right cuts are performed 3 times each, the V-belt is performed 5 times, and the thin pass is performed 3 times. Finally, the roll gap is adjusted to cut the sheet and the sheet thickness is controlled to be 2-3 mm.
9. The method for preparing a high heat-resistant oxidized fluorosilicone rubber material according to claim 6, characterized in that, In step 6, the vulcanization temperature of the first stage of the flat vulcanizing machine is 165-175℃, the molding pressure is 10-15 MPa, and the vulcanization pressing time is 12-15 minutes.
10. The method for preparing a high heat-resistant oxidized fluorosilicone rubber material according to claim 6, characterized in that, In step 7, the heating procedure for the two-stage vulcanization is as follows: first, maintain the temperature at 100°C for 1 hour, then raise the temperature to 200°C within 30 minutes, and maintain the temperature at 200°C for 4 hours.